A quality control study on Premium Agro-Vet Corporation - Blanco, Mariel M.; Braga, Virginia P.; Maluenda, Jo-Ann. (Diliman, Quezon City College of Engineering, 2000)
This study a Quality Control study on Premium Agro-Vet Corporation, in fulfillment to the requirements of the IE 135 course on quality control. The study focused on PRIMACLINE SOLUBLE POWDER, one of the products manufactured by the company. PRIMACLINE is a water soluble antibiotic that treats diseases of poultry and livestock. The study fully documents the product in focus, including complete documentation of its production process. Using the tools discussed in the course, the quality aspects of the production process were analyzed. Through the Stramline analysis, three main problem areas were identified : Low potency of the product, Overdosage and Advanced Spoilage of the Product. Low potency of the product means that the antibiotic is weak when administered to the animals affected with disease. Upon analysis of the process (using the ISHIKAWA and PARETO diagrams), it was found that there are several possible causes for the product to have low potency : Contamination of active ingredients, Inaccurate measurement of raw materials, non-homogeneity of the products and inadequate storage facilities. Overdosage on the other hand, is when the antibiotic is too potent. This may cause damage to animal wealth when administered. Possible situations found to cause overdosage are : Contamination of active ingredients and inaccurate measurement of raw materials. The third problem area identified is the advanced spoilage of the product. The finished product is a free flowing powder and should remain dry and must not clump together. Advanced spoilage is when the product retains too much moisture, having a "caking" effect, thus is unusable to the consumer. The causes of this as cited from the analysis are : Inaccurate measurement of the anti-caking ingredients, non-homogeneity of the product, improper storage during the process and improper storage by the consumer. Since the problem areas have similar causes, the search for alternatives were focused on these causes. To eliminate contamination of active ingredients, it is suggested that the workers be issued protective clothing. Also, a layout of the mixing area was proposed wherein the mixing and the packaging area were separated. Another improvement in the plant layout, to help eliminate contamination is in the storage area where the quarantine area is isolated from the main storage area. Another cause that was found in more than one problem area is the inaccurate measurement of raw materials used in mixing. To solve this, it is recommended that the workers work in pairs for easier detection of errors in measurement. To eliminate non-homogenity of a product, it is recommended that the mixing process use an average mixing time per product. This average mixing time can be computed through sampling and statistical computations. Temperature control is another factor that can help eliminate non-homogenous products. The improvement in the mixing area layout will help control the temperature. The approach of the study to address the main causes, especially those that appear in more than one problem area, help to generate more effective alternatives.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 135 : Industrial Quality Control
Keywords: Premium Agro-Vet Corporation; Quality control